Influence of sintering temperature on dielectric and piezoelectric properties of B2O3 doped lead-free Ba(Ti 0.9Sn0.1)O3 ceramics - Tawichai N. (2014)
Lead-free ceramics of Ba(Ti0.9Sn0.1)O3 doped with 0.5 wt% B2O3 were prepared by a conventional solid state sintering method. Dielectric and piezoelectric properties of the ceramics were investigated as a function of sintering temperature. Although density of the ceramics was observed to decrease with increasing the sintering temperature, the sample sintered at 1350°C showed maximum dielectric constant of 9900 at the phase transition temperature ∼36°C. Higher relative tunability of 83% was also observed at the same condition. However, the ceramics showed a lower piezoelectric coefficient (d33) at a higher sintering temperature. Copyright © Taylor & Francis Group, LLC.